An electro-physiological device to assess status of vitreous transparency - Gupta, Meenakshi; Gupta, Y; Singh, PN (Nepalese Journal of Ophthalmology, 2011)
Introduction: Evaluation of optical media is important in ophthalmic practice. Objective: to design and tryout an electro-physiological device in order to assess the transparency of the vitreous. Materials and methods: A media-meter was designed where a light sensitive sensor was placed on the cornea and adjoining sclera during the process of trans-illumination. The trans-corneal (TC) and trans-scleral (TS) light transmittance were recorded objectively. By standardizing these readings on normal eyes, it was possible to suspect any cause of vitreous turbidity in eyes where the transmittance of light was observed to be less than the normal readings. Statistics: Media-meter values were compared using Student’s unpaired t- test for comparison between both the groups. Pearson or Spearman correlation coefficients were calculated for pooled media-meter values obtained from patients with endophthalmitis. Results: The readings were obtained by TC and TS media-metry with white light in 20 eyes that served to standardize the device. The mean values for the intensity recorded on the media-meter were 206 to 74 Lux and after log-values conversion were 2.14 (range 2.36 to 1.87) and 45 to 31 Lux and after log conversion 1.60 (range 1.66 to 1.49) for TC and TS media-meter respectively. There was a highly significant difference between normal eye readings and the corresponding values obtained for TC and TS media-meter values in eyes with endophthalmitis. Conclusion: The media-meter can be used to evaluate vitreous transparency. Key words: trans-illumination; media-meter; endophthalmitis; vitreous transparency DOI: 10.3126/nepjoph.v3i1.4278Nepal J Ophthalmol 2011;3(5):45-48